2019
DOI: 10.1002/aenm.201901188
|View full text |Cite
|
Sign up to set email alerts
|

Na3V2(PO4)3 as the Sole Solid Energy Storage Material for Redox Flow Sodium‐Ion Battery

Abstract: like wind and solar for electricity generation. The growth will go on accelerating to replace the fossil fuels in the future. [1] At the same time, the intermittent nature of these power sources necessitates a durable and cost-effective energy storage system to meet the huge demands for peak shifting and power buffering for GWscale systems. Considering the scalability, operation safety, and flexibility, redox flow battery (RFB) is regarded as one of the most promising electrochemical energy storage technologie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 51 publications
0
19
0
Order By: Relevance
“…This resulted in a demonstrated volumetric energy density of 88 Wh L À 1 and a solid storage capacity of 52 %. [80] The authors also observed an [80] improvement in electron transfer kinetics over previous systems.…”
Section: Recent Advancesmentioning
confidence: 81%
“…This resulted in a demonstrated volumetric energy density of 88 Wh L À 1 and a solid storage capacity of 52 %. [80] The authors also observed an [80] improvement in electron transfer kinetics over previous systems.…”
Section: Recent Advancesmentioning
confidence: 81%
“…6a). The Na 3 V 2 (PO 4 ) 3 /rGO has been widely explored and used as a promising cathode material for SIBs owing to its excellent work voltage and superior cycling stability [53,[58][59][60]. SEM images and XRD pattern of the as-synthesized Na 3 V 2 (PO 4 ) 3 /rGO are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[13] This feature may allow a high SMRT reaction rate since it has been suggested to be limited by the ion diffusion in the solid matrix in the actual working conditions. [39,26] Volume-unbalanced while compositionally symmetric cells were fabricated to evaluate the catholyte performance and NiHCF utilization without crossover interference. As shown in the Supporting Information, Figure S11, the elongated voltage profile was a result of the two-way SMRT reactions of NiHCF-NaI/NaI 3 .…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[21][22][23] The redox-targeting reactions, where solid materials are used as capacity boosters in the energy storage tank (Figure 1 a; Supporting Information, Figure S1), have been demonstrated as an efficient method to considerably improve the effective solubility of redox species in various RFBs such as nonaqueous redox flow lithium or sodium batteries and metal complex-based aqueous RFBs, and so on. [24][25][26][27][28] In this study, the redox targeting reaction of quinone with polyimide was investigated to solve the low-solubility hurdle of 2,7-AQDS in pH-neutral electrolyte system.…”
mentioning
confidence: 99%